PENGARUH HUMAN RELATION DAN REWARD TERHADAP KINERJA KARYAWAN PADA PT. JALUR NUGRAHA EKAKURIR PEKANBARU - Nur Fadli; Jumiati Sasmita; Marzolina ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT. Jalur Nugraha Ekakurir Pekanbaru located on the street Sisingamaraja No. 65 Pekanbaru Riau in order to determine and analyze the influence of human relations and reward partially on the performance of employees at PT. Jalur Nugraha Ekakurir Pekanbaru. To know and analyze the influence of human relations and simultaneously reward the performance of employees at PT. Jalur Nugraha Ekakurir Pekanbaru. The study population was 43 employees of PT. Nugraha lane Ekakurir Pekanbaru. Research variables used are human relations and reward as the independent variable and the performance of employees as the dependent variable. Methods of data analysis using multiple linear regression analysis aided by SPSS 20 for windows. The results of this study indicate that human relations and reward partially and simultaneously have a significant influence on the performance of employees of PT. Jalur Nugraha Ekakurir Pekanbaru. The dominant variable affecting the performance is a factor of human relations. Research that has been conducted in accordance with the regression test (t test) and (f test) shows independent variables studied are human relations and reward variables have a significant effect on the dependent variable employee performance. Recommendations to the authors propose is expected to PT. Jalur Nugraha Ekakurir Pekanbaru to be able to further enhance the variable human relations as establish effective communication, shared interests with the employees, a positive view of employees, establish a harmonious relationship with employees and provide tolerance among its members, because human relations greatly affect the performance by gaining average responses agreed.Keywords: Human Relations, Reward and Performance